If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + (-11y) = 0 Combine like terms: 3y + (-11y) = -8y -8y = 0 Solving -8y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-8'. y = 0 Simplifying y = 0
| 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 | | -15t-9+8t=4t-3 | | 4+-1x=-1x+4 | | 0.5x-0.1=0.4-0.6(9-2x) | | 3y-7=2y+5 | | 3-6x=-80-5x | | 4+-1x=1x+4 | | x^2+1x=272 | | -2y+8=3y+28 | | 6x^24= | | 3x+1.5x+x+180=455 | | 6(4x-3)-10= | | 7x+9x-69=46-7x | | 2(9x-1)=99-7(3-4k) | | 8n-3.5=-20 | | z/2+1=7z/2 | | 10(1+30b)=-20 | | 2x+8-k=-3 | | 24-4= | | 20z+80=140+10x | | -(3x-2)-(x+4)=-(2x-2)-(2x+4) | | 10+30b=-2 | | 11520=32x^2+64x | | 9x-4x-15=-35 | | 2(6x)+2(8x-10)= | | -17=-1x+2x-7 | | 4-3x=-2x | | 0.5b+4=29(b+2) | | -2y+3(4-y)=12 | | 7x-9(-21-3x/7)=63 |